2014
DOI: 10.1080/07315724.2013.862490
|View full text |Cite
|
Sign up to set email alerts
|

Serum Coenzyme Q10, α-Tocopherol, γ-Tocopherol, and C-Reactive Protein Levels and Body Mass Index in Adolescent and Premenopausal Females

Abstract: Objective Lipid-soluble antioxidants are associated with a lower incidence for many chronic diseases of aging, possibly by preventing damage from chronic inflammation. In the current study, we compared serum levels of coenzyme Q10 (CoQ10), α-tocopherol, γ-tocopherol, and C-reactive protein (CRP) between adolescent girls and premenopausal women to assess changes from childhood to midlife. Methods Baseline serum CoQ10, α-tocopherol, γ-tocopherol, and CRP levels were measured in 207 girls (13-19 years) and 183 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Similarly, CoQ 10 concentrations in human organs change significantly through the life span of individuals (25,78), with an inverted U-shape relationship between CoQ content and age, similar to that observed in rats. Thus, CoQ 10 increases three-to fivefold in the lung, heart, spleen, liver, kidney, pancreas, and adrenal glands in the first 20 years of life, and then decreases, with the spleen and pancreas reported to have lower CoQ 10 at 80 years than at birth (78).…”
Section: Age-dependent Changes To Tissue Coq Contentsupporting
confidence: 60%
“…Similarly, CoQ 10 concentrations in human organs change significantly through the life span of individuals (25,78), with an inverted U-shape relationship between CoQ content and age, similar to that observed in rats. Thus, CoQ 10 increases three-to fivefold in the lung, heart, spleen, liver, kidney, pancreas, and adrenal glands in the first 20 years of life, and then decreases, with the spleen and pancreas reported to have lower CoQ 10 at 80 years than at birth (78).…”
Section: Age-dependent Changes To Tissue Coq Contentsupporting
confidence: 60%
“…In contrast, hepatic levels of vitamin E have been found to not be significantly affected by age [29] . Other studies have reported enhanced serum concentrations of vitamin E in the elderly from 60 years [27,30,31] , which may be attributed to the age-dependent increases in serum cholesterol/lipoprotein concentrations [30] ; this may be protective against increased lipid peroxidation during aging [29,32] . Another explanation was given by Succari et al [31] , who suggested that life-style and age-associated changes independent of serum cholesterol/lipoprotein concentrations are responsible for the increased vitamin E levels in aged French women.…”
Section: Intestinal Absorptionmentioning
confidence: 99%
“…In contrast, Gunanti et al [34] found inverse associations between BMI and serum α-TOH concentrations adjusted for total cholesterol, i.e., the α-TOH:total cholesterol ratio in Mexican-American children of the United States NHANES study. In addition to the association between BMI and α-TOH, BMI has also been positively associated with serum γ-TOH concentrations [32] . It has been observed in several studies that smoking affects serum levels of antioxidants, such as vitamin E. For example, Al-Azemi et al [33] and Shah et al [38] observed that smokers had lower serum concentrations of α-TOH compared to non-smokers.…”
Section: Intestinal Absorptionmentioning
confidence: 99%
“…Coenzyme Q 10 (CoQ 10 ) plays a crucial role in mitochondrial bioenergetics, including ATP production [5,6]. Furthermore, CoQ 10 could act as an antioxidant, preventing oxidative damage of lipids, proteins and DNA [7,8].…”
Section: Introductionmentioning
confidence: 99%